PENINGKATKAN PRESTASI BELAJAR MENGGUNAKAN ALAT-ALAT UKUR MELALUI PENGGUNAAN MEDIA KOMPUTER - Sugiyanti, Sugiyanti (Jurnal Penelitian Pendidikan, 2012)
Competency of using measurement tools is one of difficult subjects to understand quickly. It was proven by the researcher and the researcherâs partner that the studentsâ learning achievement has not met the satisfaction yet. There were still many students obtained the score under the passing grade (KKM). Media of learning is an important element in the process of teaching and learning. One of the appropriate media is computer. With this media, the students can show the identification of measurement tools, know the measurement tools, and treat the measurement tools so that it helps the students to understand the subject. This research aims at knowing the improvement of studentsâ learning achievement in the activities of teaching and learning in using the measurement tools through the media of computer on tenth grade students of TKR 2 SMKN 7 Semarang. This classroom action research was conducted in two cycles. In every cycle, it consists of planning, actuating, observing, and reflecting. The data used in this research are: 1). Quantitative data, which was comparing the result of studentsâ learning achievement in the cycle I and cycle II. 2). Qualitative data analysis qualitative, in the compared the result of observation on the studentsâ activities during teaching and learning process and the studentsâ response or feed back toward the use of computer media in both, cycle I and II. This research resulted that there was improvement on studentsâ learning activities of 75, 49% (good) in the cycle I and it increased into 86% (very good) in the cycle2. And the studentsâ response toward the use of computer media in teaching and learning process, it resulted agree in the cycle I and changed into very agree in cycle II. From those data, the researcher concluded that there was significant improvement of studentsâ learning achievement, in which it was obtained 20% of students passed the KKM in Pre-Cycle, then in the Cycle I, the number of students who passed the KKM reached 40 %, and in the Cycle 2, the students who passed the KKM reached 100 %.